Mass Propagation of Dendrocalamus Giganteus Wall. Ex Munro Through in Vitro Culture (Bangladesh Journal of Botany, 2023)
The present experiment was conducted to establish an efficient protocol for mass propagation of Dendrocalamus giganteus Wall. ex Munro through in vitro culture using nodal segments as explants. The highest percentage of shoot induction (86.67 %) was obtained in the liquid MS medium supplemented with 1.5 mg/l BAP and 1.0 mg/l TDZ with maximum number of shoots (3.91 ± 0.87) per explant. The highest number and length of shoots were 22.83 ± 1.30 shoots/culture and 7.71 ± 0.96 cm, respectively induced on agitated liquid MS medium supplemented with 2.0 mg/l BAP and 1.0 mg/l TDZ. Incorporation of 8 % coconut water in the above mentioned medium resulted satisfactory shoot growth and development. The best response towards root induction (90 %) was observed when 3-4 shoots clump were transferred onto halfstrength of gelled MS medium fortified with 4.0 mg/l IBA with 9.31 ± 1.45 roots per unit shoot. Successful acclimatization of well-rooted clumps of 4-5 shoots was achieved in a mixture of soil, sand, and compost (1 : 1 : 1) with 90% survival rate.Bangladesh J. Bot. 52(2): 337-343, 2023 (June)